The Generation of an Artificial ATP Deficit Triggers Antibiotic Production in Streptomyces lividans - Nicolas Seghezzi; Emmanuelle Darbon; Cécile Martel; Michelle David; Clara Lejeune; Catherine Esnault; Marie-Joelle Virolle (MDPI AG, 2022)
In most Streptomyces species, antibiotic production is triggered in a condition of phosphate limitation, a condition that is known to be correlated with a low intracellular ATP content compared to growth in a condition of phosphate proficiency. This observation suggests that a low ATP content might be a direct trigger of antibiotic biosynthesis. In order to test this hypothesis, we introduced into the model strain Streptomyces lividans, a functional and a non-functional ATPase cloned into the replicative vector pOSV206 and expressed under the control of the strong ErmE* promoter. The functional ATPase was constituted by the α (AtpA), β (AtpB) and γ (AtpD) sub-units of the native F1 part of the ATP synthase of S. lividans that, when separated from the membrane-bound F0 part, bears an ATPase activity. The non-functional ATPase was a mutated version of the latter, bearing a 12 amino acids deletion encompassing the active site of the AtpD sub-unit. S. lividans was chosen to test our hypothesis since this strain hardly produces any antibiotics. However, it possesses the same biosynthetic pathways of various specialized metabolites as S. coelicolor, a phylogenetically closely related strain that produces these metabolites in abundance. Our results demonstrated that the over-expression of the functional ATPase, but not that of its mutated version, indeed correlated with the production of the bioactive metabolites of the CDA, RED and ACT clusters. These results confirmed the long known and mysterious link existing between a phosphate limitation leading to an ATP deficit and the triggering of antibiotic biosynthesis. Based on this work and the previous published results of our group, we propose an entirely novel conception of the nature of this link.